Gerakan Sadar Pengelolaan Obat Mandiri (GESPO-MANDIRI) : Edukasi DAGUSIBU pada Masyarakat Kelurahan Anduonohu Kota Kendari : Self-management Awareness Movement (GESPO-MANDIRI): DAGUSIBU Education to the Community of Anduonohu Village, Kendari City - Sida, Nurramadhani A; Henny Kasmawati; Sitti Raodah Nurul Jannah; Loly Subhiyati Idrus (POLITEKNIK BINA HUSADA KENDARI, 2025)
The public's understanding of proper medication management is critical for achieving optimal health. However, many remain unaware of correct methods for obtaining, using, storing, and disposing of medications. To address this issue, the Indonesian Ministry of Health introduced the DAGUSIBU concept. In October 2024, a community service program was conducted in Anduonohu Subdistrict, Kendari City, involving 30 randomly selected participants. Education was delivered through lectures supported by leaflet media, and participants underwent pre-tests and post-tests in a question-and-answer format. Pre-test results revealed significant gaps in knowledge about medication storage and disposal practices. The education sessions emphasized proper storage methods, including keeping medications in their original packaging, following storage instructions, avoiding direct sunlight, storing them in cool, dry places, and ensuring they are out of children's reach. Participants were also educated about monitoring expiration dates and beyond-use dates. Disposal practices were tailored to medication types: solid medications were removed from packaging and crushed, non-antibiotic syrups were poured into drains with packaging destroyed, and topical medications were separated from packaging, buried, and their packaging discarded appropriately. Post-test results indicated improved participant knowledge. The DAGUSIBU-based program successfully raised public awareness about the safe handling of pharmaceutical products. This initiative supports the Ministry of Health's efforts to foster responsible medication practices in Indonesia, contributing to safer and healthier communities